African masks : identity heritage in cultural diversity between profane and sacred spaces in Benin - (:unkn) unknown (My University, 2020)
This thesis is aimed to deal with the sociology of expertise in the african mask cultural mediation. In Benin country, it is observable that museums and performing arts do not exhibit certain categories of masks including égoungoun and abikou, while they show some others, zangbéto and guèlèdè in this case. This arouses attention, insomuch as in Porto-Novo, a city where a plurality of masks’ sanctuaries is noticed, the ethnographic museum paradoxically uses drawings to present the égoungoun and the zangbéto which on the other hand, are physically seen in exhibitions in western countries. These masks belong to two large cultural areas (adja-tado and yorouba-nago) densely present in three west african countries : Benin, Nigeria and Togo. This geographic area, but especially southern and central Benin will serve as framework for our study. It attempts to understand the sociological constraints unfavorable to some forms of mask exposure in beninese territory and whether the concerned populations can adopt a noetic openness approach and dialogue with other cultures. By doing field surveys with varied public made up of intellectuals, dignitaries of mask societies, political and adminitrative officials, religious authorities, cultural mediators, ritual traditions insiders and ordinary people that we deem, representative of the population to reveal the true faces of current popular beliefs, we hope we’ll provide social sciences with a first definition and classification of means to popularize the african mask, in a globalizing world cultural environment.
Keywords: African Research